2021
DOI: 10.1155/2021/5511598
|View full text |Cite
|
Sign up to set email alerts
|

The Gene Coexpression Analysis Identifies Functional Modules Dynamically Changed After Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is a major cause of morbidity and mortality, both in adult and pediatric populations. However, the dynamic changes of gene expression profiles following TBI have not been fully understood. In this study, we identified the differentially expressed genes (DEGs) following TBI. Remarkably, Serpina3n, Asf1b, Folr1, LOC100366216, Clec12a, Olr1, Timp1, Hspb1, Lcn2, and Spp1 were identified as the top 10 with the highest statistical significance. The weighted gene coexpression analysis (WG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…Transcriptomics studies have consistently identified major DE signatures across various TBI models, 8 , 47 , 50 , 52–58 and the limited number featuring time-course designs reveal dynamic changes across periods from the hours post-injury to months and even years later. 13 , 59–62 Our results support a previously proposed mechanistic model where surviving neurons activate a transcriptomic signature of cellular reprogramming, development, and regeneration in the aftermath of injury, 53 with relevant terms enriched here in upregulated modules ii and iv. Our findings are also in line with a study that used NanoString to profile candidate genes, finding differences in trajectories of sets of immune and inflammation genes, as well as decreased and shorter persistence of downregulation signatures post-TBI.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Transcriptomics studies have consistently identified major DE signatures across various TBI models, 8 , 47 , 50 , 52–58 and the limited number featuring time-course designs reveal dynamic changes across periods from the hours post-injury to months and even years later. 13 , 59–62 Our results support a previously proposed mechanistic model where surviving neurons activate a transcriptomic signature of cellular reprogramming, development, and regeneration in the aftermath of injury, 53 with relevant terms enriched here in upregulated modules ii and iv. Our findings are also in line with a study that used NanoString to profile candidate genes, finding differences in trajectories of sets of immune and inflammation genes, as well as decreased and shorter persistence of downregulation signatures post-TBI.…”
Section: Discussionsupporting
confidence: 87%
“…A recent microarray study included the same two time points as used here and found similar time-dependent inflammation signatures. 13 , 59 Our results are generally aligned with findings from this study, though our methods are anchored on DE changes rather than covariance and are thus by transcriptional pathology. Further, by integrating expression and H3K4me3 ChIP-seq in our comparison, we identified underlying epigenetic activation and repression of differentially expressed loci, as describe below.…”
Section: Discussionsupporting
confidence: 80%
“…The complement system is a biochemical pathway involved in both innate and adaptive immune responses and has four main functions: lysis of microorganisms, promotion of phagocytosis, triggering inflammation, and immune clearance [ 25 , 26 ]. The activation of C3 can trigger a continuous degradation mechanism to activate microglia and astrocytes, reduce the density of dendritic cells and synapses, and inhibit the migration of neuroblast cells, which leads to neuron loss after several weeks of TBI [ 27 , 28 ]. The upregulation of C3 can promote the progression of the neurodegenerative diseases, and previous studies have shown that C3 in turn interacts with the C3aR neurons and microglia to mediate β -amyloid pathology and neuroinflammation in AD mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…e complement system is a biochemical pathway involved in both innate and adaptive immune responses and has four main functions: lysis of microorganisms, promotion of phagocytosis, triggering in ammation, and immune clearance [25,26]. e activation of C3 can trigger a continuous degradation mechanism to activate microglia and astrocytes, reduce the density of dendritic cells and synapses, and inhibit the migration of neuroblast cells, which leads to neuron loss after several weeks of TBI [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…ASF1B suppression enhanced the apoptotic ability of prostate cancer cells by inactivating PI3K/Akt pathway [ 11 ]. In addition, gene expression profiles showed a significant increase in ASF1B expression following traumatic brain injury [ 12 ]. However, the influences of ASF1B on LGG have not been uncovered.…”
Section: Introductionmentioning
confidence: 99%